DIAMETER DISTRIBUTION OF THE DYNAMICS OF ARAUCARIA ANGUSTIFOLIA IN A MIXED OMBROPHILOUS FOREST FRAGMENT IN PARANÁ - SCHIKOWSKI, Ana Beatriz; MARTINS, Ana Paula Marques; SCHIAVO, Bruna Nascimento de Vasconcellos; STANG, Mariana Bussolo; CORTE, Ana Paula Dalla; PÉLLICO NETTO, Sylvio; SANQUETTA, Carlos Roberto (Brazilian Journal of Biometrics, 2016)
This work aimed to study the suitability of different models of probability distribution to characterize the diameter structure of Araucaria angustifolia (Bertol.) Kuntze in natural forest, as well as evaluating the dynamic of diameter distribution for the period 1995-2014. The data were taken from a continuous inventory of 3 permanent sample plots of 1 hectare each, located in São João do Triunfo, Parana, Brazil. Various probability density functions were adjusted to evaluate the diameter distribution of the species and the quality of the adjustments checked by the Kolmogorov-Smirnov test. The SB Johnson function presented the best performance in all years of the experimental evaluation, but with some restrictions related to the smaller diameters classes. Regarding the dynamics of distributions evaluated, the species showed a decreasing distribution at the beginning of the study period, but with a tendency to move gradually to normality, requiring a longer study period for monitoring this dynamic. There was significant statistical difference between the curves during the study period, supporting the hypothesis of a diameter distribution evolution for A. angustifolia.